2013
DOI: 10.1002/jeab.45
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting of monetary rewards over a wide range of amounts

Abstract: The present study examined delay discounting of hypothetical monetary rewards over a wide range of amounts (from $20 to $10 million) in order to determine how reward amount affects the parameters of the hyperboloid discounting function and to compare fits of the hyperboloid model with fits of two discounting models used in neuroeconomics: the quasi-hyperbolic and the double-exponential. Of the three models assessed, the hyperboloid provided the best fit to the delay discounting data. The present delay discount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
60
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 32 publications
9
60
0
3
Order By: Relevance
“…For example, both cases and controls showed significantly steeper discounting of delayed gains than of delayed losses after matching based on age, gender, and education (both t s > 7.5, both p s < .001). Moreover, consistent with previous findings (Green et al 2013b; Myerson et al 2011; for a review, see Green and Myerson 2004), the decrease in subjective value of delayed and probabilistic outcomes was well described by the hyperboloid discounting model (Myerson and Green 1995), as indicated by the low root mean square error (RMSE) of the subjective values estimated by the model.…”
Section: Resultssupporting
confidence: 88%
“…For example, both cases and controls showed significantly steeper discounting of delayed gains than of delayed losses after matching based on age, gender, and education (both t s > 7.5, both p s < .001). Moreover, consistent with previous findings (Green et al 2013b; Myerson et al 2011; for a review, see Green and Myerson 2004), the decrease in subjective value of delayed and probabilistic outcomes was well described by the hyperboloid discounting model (Myerson and Green 1995), as indicated by the low root mean square error (RMSE) of the subjective values estimated by the model.…”
Section: Resultssupporting
confidence: 88%
“…The finding that discounting decreased as reward magnitude increased (regardless of commodity) is consistent with a wide body of studies that have reported a similar decrease in discounting with increasing reward magnitudes (e.g. Green, Myerson & McFadden, 1997; Green et al, 1994; Green, Myerson, Oliviera, & Chang, 2013; Johnson & Bickel, 2002; Kirby, 1997). In addition, changes in discounting across treatment differed by commodity.…”
Section: Discussionsupporting
confidence: 88%
“…For example, energy drink users were more likely to be male, 2,5,8,11 employed, 13 have higher AUDIT scores, 3 and they were more likely to engage in various risk behaviors. [2][3][4][5][6][7][8][9][10][11]13,14 In addition, results from the delay discounting tasks replicated results from studies that found that larger monetary rewards are discounted less steeply than smaller rewards 47 and delay discounting of condom-protected sex is steeper when partners are perceived as more desirable and less likely to have an STI. [29][30][31][32][33] The results of this study should be interpreted within the context of several limitations.…”
Section: Discussionsupporting
confidence: 74%
“…47 Also replicated was the finding that overall proportion of larger-later choices was highly correlated with mean log 10 k (r = À0.99, p < 0.0001). 42 Weekly energy drink users had higher mean log 10 k values than less-than-weekly energy drink users (M = À1.79, SD = 0.66 vs. M = À2.04, SD = 0.69, p < 0.0001), indicating steeper discounting of delayed monetary rewards, and they chose a significantly lower proportion of larger-later rewards than less-than-weekly energy drink users (M = 0.40, SD = 0.18 vs. M = 0.46, SD = 0.19, p < 0.0001).…”
Section: Resultssupporting
confidence: 66%